Argentina vs holdouts: The complete saga (2005-2016) - Rosario Bustillo; Tomás A. Marinozzi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
This paper provides a deep analysis into the legal dispute between Argentina and the holdouts as a consequence of the 2001 sovereign default. This paper highlights how the legal conflict helped uncover fundamental issues in the sovereign debt restructuring mechanism (SDRM). Questions regarding overarching injunctions, ambiguous interpretation of boilerplate clauses and the arguable judicial overreach of foreign court lead to necessary changes on standard clauses in sovereign debt contracts. A multidisciplinary approach combining aspects of law and economics was applied in order to fully appreciate the complexity of the subject, as well as the impact this particular case had on posterior sovereign debt contracts.
Keywords: F34; H63; G01; K00; 330; Sovereign Debt Restructuring; Holdouts; Pari Passu